Comparison of Femoral Component Rotation between Robotic-Assisted vs. Soft-Tissue Tensor Total Knee Arthroplasty with Anatomic Implants - Bartosz M. Maciąg; Tomasz Kordyaczny; Grzegorz J. Maciąg; Marcin Łapiński; Dawid Jegierski; Jakub Świderek; Hanna Tsitko; Monika Dorocińska; Krystian Żarnovsky; Maciej Świercz; Piotr Stępiński; Olga Adamska; et al. (Medicina, 2023)
Background and Objectives: Total knee arthroplasty (TKA) is the most effective treatment method for end-stage osteoarthritis. One of the most important aspects of this surgery is adequate implant positioning, as it guarantees the desired outcome of restoring limb biomechanics. Surgical technique is being continuously improved along with hardware development. There are two novel devices designed to help establish proper femoral component rotation: soft-tissue tensor and robotic–assisted TKA (RATKA). This study compared the femoral component rotation achieved with the use of three methods: RATKA, soft tissue tensioner and the conventional measured-resection technique, all of them utilizing anatomical design prosthesis components. Materials and Methods: A total of 139 patients diagnosed with end-stage osteoarthritis underwent total knee arthroplasty between December 2020 and June 2021. After the surgery, they were divided into three groups depending on procedure technique and implant type: Persona (Zimmer Biomet) + Fuzion Balancer, RATKA + Journey II BCS or conventional TKA + Persona/Journey. Postoperatively, a computed tomography examination was performed in order to measure femoral component rotation. All three groups were compared independently during statistical analysis. Fisher’s exact, Kruskal–Wallis and Dwass–Steel–Crichtlow–Fligner tests were used for particular calculations. Results: Statistically significant differences in femoral component rotation between groups were noticed. However, in terms of values other than 0° in external rotation, no significant variance was revealed. Conclusions: Additional total knee arthroplasty instruments seem to improve the outcomes of the surgery, providing better component positioning than in the conventional measured-resection technique based only on bone landmarks.